Inkubationstemperaturens effekt på gälslagsfrekvens (metabolism) hos lax (Salmo salar) - Nilsson Saldías, Mikael (Karlstads universitet, Fakulteten för hälsa, natur- och teknikvetenskap (from 2013), 2020)
According to the Intergovernmental Panel on Climate Change (IPCC), the temperatures on Earth will increase by up to 5°C during this century, and in particular during winter at northern latitudes. Temperature influences ectotherms, like fish, in many different ways. The eggs of salmon, for example, develop during the winter, and previous work has shown that juvenile salmon grow faster if they experience warm incubation temperatures as eggs as compared to juvenile salmon that experience cold incubation temperatures. A possible explanation could be that metabolic rates could be reduced for salmon that experience warm incubation temperatures as eggs. The goal of this project was to examine whether this is correct. To do so, salmon eggs were subjected to three different temperature regimes: a control treatment with natural temperature conditions, a treatment with elevated temperature, and a mixed temperature treatment, where eggs were incubated in elevated temperature until the beginning of January, and thereafter exposed to natural conditions. Ventilation rate was measured, since previous studies have shown that ventilation rate is a proxy for metabolism. Also fish activity and body size were measured. The results showed no significant effect of incubation temperature on ventilation rate, nor did activity or body size affect ventilation rate. The results regarding fish activity and body size are uncertain in this case. Therefore, further studies are appropriate. Studies, like this one, on physiological traits and how they are influenced by climate change, are crucial for the conservation of biodiversity. Enligt FN:s klimatpanel (IPCC) kommer temperaturerna på jorden att stiga med upp till ca 5°C under detta sekel, i synnerhet på vintern och på nordliga breddgrader. Temperatur påverkar ektotermer, exempelvis fiskar, på många olika sätt. Laxen har, till exempel, ägg som utvecklas under vintern och tidigare studier har visat att juvenila laxar växer fortare efter att ha utsatts för varmare temperaturer under ...